A quantitative study of attitudes toward the research participation of adults with intellectual disability: Do stakeholders agree?. Issue 3 (July 2018) - ; Carroll, Anna; Cuddy, Marty; Feldman, Micah Fialka; Flanigan, Daniel; Fratangelo, Patricia; Gonzalez, Lance; Kennedy, Michael; King, Kathleen; Mansfield, Christopher; McGowan, Deborah; Romer, Rachel; et al.
Abstract: Background: Attitudes toward the research participation of adults with intellectual disability inform research policy and practice, impact interest in and support for research participation, and promote or discourage the generation of new knowledge to promote health among adults with intellectual disability. Yet we know little about these beliefs among the public and the scientific community. Objective/Hypothesis: We quantitatively studied attitudes among adults with intellectual disability, family and friends, disability service providers, researchers, and Institutional Review Board (IRB) members. We predicted that adults with intellectual disability, and researchers would espouse views most consistent with disability rights, whereas IRB members, and to a lesser degree family, friends, and service providers, would espouse more protective views. Methods: We surveyed five hundred and twelve members of the five participant stakeholder groups on their attitudes toward the research participation of adults with intellectual disability. Results: We found broad support for research about people with intellectual disability, though slightly more tempered support for their direct participation therein. In general, IRB members and to some extent adults with intellectual disability endorsed direct participation less than others. We also found that adults with intellectual disability strongly believed in their consent capacity. Conclusions: Resources should be directed toward health-related research with adults with intellectual disability, and interventions should be pursued to address ethical challenges and promote beliefs consistent with human rights.